2008
DOI: 10.1089/cap.2007.0026
|View full text |Cite
|
Sign up to set email alerts
|

Striatal Volume Abnormalities in Treatment-Naïve Patients Diagnosed with Pediatric Major Depressive Disorder

Abstract: These findings provide fresh evidence for abnormalities in the striatum of medication-naïve pediatric MDD patients and suggest the possible involvement of the striatum in the pathophysiology of MDD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
51
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 37 publications
9
51
1
1
Order By: Relevance
“…The GM regions detected here in juveniles with subthreshold depression have been implicated in the pathophysiology of depression in adults and adolescents, [9][10][11]14,29 and altered WM microstructure within tracts connecting these regions has been reported in adolescents with MDD. 37 Also, functional impairments within the reward system have been hypothesized to contribute to the onset of depressive disorders in adolescence.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The GM regions detected here in juveniles with subthreshold depression have been implicated in the pathophysiology of depression in adults and adolescents, [9][10][11]14,29 and altered WM microstructure within tracts connecting these regions has been reported in adolescents with MDD. 37 Also, functional impairments within the reward system have been hypothesized to contribute to the onset of depressive disorders in adolescence.…”
Section: Discussionmentioning
confidence: 56%
“…The differences are more widespread in adolescents with MDD, since reduced gray matter volumes have been reported in frontal, limbic, and striatal regions such as prefrontal cortex (PFC), 9,10 ACC, 11 amygdala, 12 hippocampus, 13 and caudates. 9,14 A sex effect was reported in one study demonstrating smaller nucleus accumbens in girls with depression only, and increased growth of the amygdala during adolescence associated with depression in girls and decreased growth in boys. 15 A further step requires investigating the morphometry on the whole brain and assessing the clinical outcome of adolescents with subthreshold depression in order to shed light on the early brain structure variations involved in such emotional dysregulation and vulnerability to depressive disorders, including vulnerability related to sex.…”
Section: Introductionmentioning
confidence: 97%
“…Depression-associated differences in BG volumes are less consistent in samples of both younger adults 19,20 and adolescents. 21 It appears, therefore, that this discrepancy is associated with age differences in the study samples; that is, it is possible that only older individuals with MDD exhibit abnormally reduced putamen and caudate volumes. In this context, it is similarly possible that MDD-related BG volumetric reductions are associated with length of MDD history, a clinical characteristic that is likely to be associated with age.…”
Section: Introductionmentioning
confidence: 98%
“…Depression-associated differences in BG volumes are less consistent in samples of both younger adults 19,20 and adolescents. 21 It appears, therefore, that this discrepancy is associated with age differences in the study Background: Growing evidence indicates that major depressive disorder (MDD) is characterized by accelerated biological aging, including greater age-related changes in physiological functioning. The disorder is also associated with abnormal neural reward circuitry, particularly in the basal ganglia (BG).…”
mentioning
confidence: 99%
“…Striatal alterations of these earlyonset patients might suggest that deficits of putaminal volumes might start from the onset of MDD. 30 Reduced brain activities of putamen toward reward stimuli are found in MDD patients, and reduced volumes of caudate were associated with severity of symptoms, which suggested that the basal ganglion might be responsible for hedonic motivation. 31 Our previous article also shows volumetric alterations of thalamus in the patients with MDD-and-PD, which also supports the findings in this study.…”
Section: Discussionmentioning
confidence: 99%